Critical views on postpartum care expressed by new mothers - Waldenström Ulla; Rudman Ann (BMC, 2007)
Abstract Background Women's evaluation of hospital postpartum care has consistently been more negative than their assessment of other types of maternity care. The need to further explore what is wrong with postpartum care, in order to stimulate changes and improvements, has been stressed. The principal aim of this study was to describe women's negative experiences of hospital postpartum care, expressed in their own words. Characteristics of the women who spontaneously gave negative comments about postpartum care were compared with those who did not. Methods Data were taken from a population-based prospective longitudinal study of 2783 Swedish-speaking women surveyed at three time points: in early pregnancy, at two months, and at one year postpartum. At the end of the two follow-up questionnaires, women were asked to add any comment they wished. Content analysis of their statements was performed. Results Altogether 150 women gave negative comments about postpartum care, and this sample was largely representative of the total population-based cohort. The women gave a diverse and detailed description of their experiences, for instance about lack of opportunity to rest and recover, difficulty in getting individualised information and breastfeeding support, and appropriate symptom management. The different statements were summarised in six categories: organisation and environment, staff attitudes and behaviour, breastfeeding support, information, the role of the father and attention to the mother. Conclusion The findings of this study underline the need to further discuss and specify the aims of postpartum care. The challenge of providing high-quality follow-up after childbirth is discussed in the light of a development characterised by a continuous reduction in the length of hospital stay, in combination with increasing public demands for information and individualised care.